Nexus between Child labor, Sector-specific Growth and International Trade in Pakistan - Sana Suleman; Sana Suleman; H. Nouman Siddique (Journal of Business & Tourism, 2021)
This study focused on analyzing the impacts of different sectors’ growth and globalization on child labor in Pakistan. The order of integration variables was found mix as some were I(0) and some were I(1). That’s why, the long run and short run dynamics were evaluated through ARDL mechanism using data from 1980-2014. The long run and short run inferences revealed that growth reduced child labor significantly in all sectors except services. The urban population growth significantly lessened the child labor as compared to rural population. The FDI significantly decreased the child labor growth while trade openness did opposite. Results suggest that trade policy and labor laws of ILO should be implemented.